2008
DOI: 10.1186/1748-7161-3-14
|View full text |Cite
|
Sign up to set email alerts
|

A Dutch guideline for the treatment of scoliosis in neuromuscular disorders

Abstract: Background: Children with neuromuscular disorders with a progressive muscle weakness such as Duchenne Muscular Dystrophy and Spinal Muscular Atrophy frequently develop a progressive scoliosis. A severe scoliosis compromises respiratory function and makes sitting more difficult. Spinal surgery is considered the primary treatment option for correcting severe scoliosis in neuromuscular disorders. Surgery in this population requires a multidisciplinary approach, careful planning, dedicated surgical procedures, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 74 publications
1
38
0
8
Order By: Relevance
“…This pattern of scoliosis progression was also pointed out by Nadeau et al 13. Development of scoliosis in Duchenne muscular dystrophy, on the other hand, is strongly related to the loss of walking ability 18. In Duchenne muscular dystrophy, typically, scoliosis is not evident in ambulatory patients and starts after patients become wheelchair dependent.…”
Section: Discussionmentioning
confidence: 52%
“…This pattern of scoliosis progression was also pointed out by Nadeau et al 13. Development of scoliosis in Duchenne muscular dystrophy, on the other hand, is strongly related to the loss of walking ability 18. In Duchenne muscular dystrophy, typically, scoliosis is not evident in ambulatory patients and starts after patients become wheelchair dependent.…”
Section: Discussionmentioning
confidence: 52%
“…They advocated the use of a sitting type orthosis for patients who reject surgery for improvement of sitting comfort. 1 In contrast, Kotwicki et al (2008) observed that a correctly designed orthosis was able to partially correct the spinal curvature and pelvic obliquity, provide a stable sitting position, balance the trunk, facilitate breathing, discharge the abdomen, and unload soft tissues of the buttocks. 12 In the present study, an improvement of 5 degrees in Cobb angle and 3 degree in Ferguson angle was observed in A-P radiogram analysis for brace on and brace off conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Havia um limiar baixo para a solicitação de raio X da coluna ou encaminhamento para um cirurgião de coluna vertebral para uma avaliação inicial. O tratamento conservador da escoliose incluía uso de colete, e, em casos graves, cirurgias de fixação e de fusão da coluna eram realizadas [17][18][19] . A osteopenia era comum nos meninos com DMD, e o efeito adicional dos esteroides orais aumentava a incidência de osteoporose e de fraturas da coluna vertebral, assim como de outras fraturas 20,21 .…”
Section: Esqueléticounclassified